2009
DOI: 10.1111/j.1600-6143.2009.02621.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Severe von Willebrand Factor/ADAMTS13 Dysbalance During Orthotopic Liver Transplantation

Abstract: Patients with liver disease show profound changes in their hemostatic system, which may further change during liver transplantation. We previously demonstrated that highly elevated levels of the platelet adhesive protein von Willebrand factor (VWF) in patients with cirrhosis lead to an increased VWF-dependent platelet deposition under flow as compared to healthy controls. In this study we examined VWF parameters during the course of liver transplantation. We collected serial plasma samples from 20 patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 29 publications
4
65
0
Order By: Relevance
“…49 Hepatic artery thrombosis after liver transplantation has long been considered a surgical complication, but recent laboratory and clinical data have implicated a role for hypercoagulation in the occurrence of these thrombotic events. [50][51][52][53] Intrahepatic thrombus formation has been demonstrated in patients with cirrhosis and also in patients with acute liver failure. 54,55 These microthrombi are believed to play a key role in progression of fibrosis as a result of local ischemia, a process referred to as parenchymal extinction.…”
Section: Clinical Evidence Of Hypercoagulationmentioning
confidence: 99%
“…49 Hepatic artery thrombosis after liver transplantation has long been considered a surgical complication, but recent laboratory and clinical data have implicated a role for hypercoagulation in the occurrence of these thrombotic events. [50][51][52][53] Intrahepatic thrombus formation has been demonstrated in patients with cirrhosis and also in patients with acute liver failure. 54,55 These microthrombi are believed to play a key role in progression of fibrosis as a result of local ischemia, a process referred to as parenchymal extinction.…”
Section: Clinical Evidence Of Hypercoagulationmentioning
confidence: 99%
“…We have previously reported on the progressive changes in hemostatic function of patients undergoing a liver transplantation (6,7). In these studies, we have found that the coagulation/ anticoagulation equilibrium shifted toward "hypercoagulability" during the procedure.…”
Section: Development Of a Hypercoagulable Status In Patients Undergoimentioning
confidence: 79%
“…In acquired TTP (aTTP), severe ADAMTS13 deficiency is due to circulating anti-ADAMTS13 autoantibodies, which act as functional inhibitors in most patients. 1-3 TTP has been described after liver transplantation (LT), [4][5][6][7][8][9] but this is, to the best of our knowledge, the first report in which aTTP is associated with pretransplant acute-on-chronic liver failure (ACLF) and no preoperative or perioperative thrombotic complications.…”
mentioning
confidence: 99%
“…In the other cases reported to date, low ADAMTS13 activities were observed both before and after LT without any measurable inhibitors. [4][5][6][7][8][9] Cirrhosis is associated with impaired innate and acquired immune responses. 13,14 Although the mechanism is unclear, we hypothesize that dysimmunity due to cirrhosis, possibly exacerbated by Fusobacterium infection, might have triggered a misrouted immune response leading to the production of inhibitory anti-ADAMTS13 autoantibodies.…”
mentioning
confidence: 99%